Genetic Diversity of the root‐knot nematode Meloidogyne enterolobii in Mulberry Based on the Mitochondrial COI Gene. Issue 12 (1st June 2020) - Shao, Hudie; Zhang, Pan; You, Chunping; Li, Chuanren; Feng, Yan; Xie, Zhenwen
Abstract: This study explores the genetic diversity and structure of Meloidogyne enterolobii in mulberry in China. The COI mitochondrial gene (mtCOI) in M.enterolobii populations in Guangdong, Guangxi, and Hunan Provinces was PCR‐amplified, sequenced, and analyzed for genetic diversity. The total number of variations, haplotypes (Hap), the average number of nucleotide differences (k), haplotype diversity (H), and nucleotide diversity (π) of mtCOI were 25, 11, 4.248, 0.900, and 0.00596, respectively. Insignificant differences in Fst value (0.0169) and a high level of gene flow (7.02) were detected among the 19‐mulberry root‐knot nematode populations, and high genetic variation within each population and a small genetic distance among populations were observed. Both phylogenetic analyses and network mapping of the 11 haplotypes revealed a dispersed distribution pattern of 19 mulberry root‐knot nematode populations and an absence of branches strictly corresponding to the 19 range sampling sites. The neutrality test and mismatch analysis indicated that mulberry root‐knot nematode populations experienced a population expansion in the past. The analysis of molecular variance (AMOVA) revealed that the genetic differentiation of M. enterolobii was mainly contributed by the variation within each group. No significant correlation was found between the genetic distance and geographical distance of M. enterolobii populations. The findings of this study provide a profound understanding of the M. enterolobii population and will inform the development of strategies to combat and manage root‐knot nematodes in mulberry. Abstract : This study explores the genetic diversity and structure of Meloidogdyne enterolobii (M. enterolobii) in mulberry in China. The mitochondrial COI gene (mtCOI) in mulberry root‐knot nematode populations in Guangdong, Guangxi, and Hunan Provinces was PCR‐amplified, sequenced, and analyzed for genetic diversity.